Copia LTR-retrotransposon superfamily occurrence and distribution and its role in the nuclear and chromosomal DNA content variations in two Passiflora species - Vieira, Ariane Tonetto (2018)
Similar to other Passiflora species, nuclear DNA content variation occurs between Passiflora edulis and Passiflora quadrangularis, which show the same 2n chromosome number. For some species, this variation accumulates distinctly in the chromosomes, with retrotransposable elements being considered one of the causes for this observed variation. LTR-retrotransposons (LTR-RT) constitute a substantial portion of the genomes, playing an important role in karyotype evolution. This study aims to investigate the occurrence and distribution of the Copia LTR-RT superfamily in P. edulis and P. quadrangularis chromosomes, and to understand the role of these sequences in nuclear and chromosomal DNA content variations. The karyotypes showed the same chromosome number, predominance of metacentric and submetacentric chromosomes, as well as 18S rDNA in the terminal portion of the short and long arms of two chromosomes, corroborating the monophyletic origin of the species. The role of LTR-RT in karyotype evolution was evidenced by differences in nuclear and chromosomal DNA content between the species as well as differently and randomly distributed retroelements between all chromosomes. Unambiguous identification of each chromosome by morphometry, 18S rDNA, DNA content and LTRRT allowed us to show that there is no relation between the total length and DNA content for some chromosomes. This phenomenon occurred in P. edulis chromosomes 2 and 6 in relation to chromosomes 1 and 5, respectively, and in P. quadrangularis chromosome 8 compared to 7. Using refined cytogenetic approaches, we analyzed each chromosome of P. edulis and P. quadrangularis individually, finding that karyotype changes were promoted by LTR retrotransposons.